Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/1871520616666160310143828
|View full text |Cite
|
Sign up to set email alerts
|

Fab(nimotuzumab)-HYNIC-99mTc: Antibody Fragmentation for Molecular Imaging Agents

Abstract: Finally, fast blood clearance nimotuzumab is a humanized monoclonal antibody that recognise, with high specific affinity, the epidermal growth factor receptor (EGF-R) which play an important role in the growth process associated with many solid tumors. In this work, the whole antibody was digested with papain in order to generate a Fab fragment, derivatized with NHS-HYNIC-Tfa and radiolabel with technetium-99m (99mTc) as a potential agent of molecular imaging of cancer. Both, whole and fragment radiolabels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…5,6 A detailed literature survey on immuno-PET/SPECT imaging agents demonstrates the magnitude of work carried out in this direction. MAb fragments labeled with radioisotopes such as 99m Tc, 64 Cu, and 111 In [7][8][9][10][11] have been evaluated for their potential applications in the diagnosis of various cancers. [7][8][9][10][11] In this regard, Tang et al reported that 99m Tc-HYNIC-trastuzumab-Fab allowed imaging as early as 2 hours and more clearly at 6 and 24-hour postinjection, thereby permitting imaging of breast tumors within the useful lifetime of 99m Tc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A detailed literature survey on immuno-PET/SPECT imaging agents demonstrates the magnitude of work carried out in this direction. MAb fragments labeled with radioisotopes such as 99m Tc, 64 Cu, and 111 In [7][8][9][10][11] have been evaluated for their potential applications in the diagnosis of various cancers. [7][8][9][10][11] In this regard, Tang et al reported that 99m Tc-HYNIC-trastuzumab-Fab allowed imaging as early as 2 hours and more clearly at 6 and 24-hour postinjection, thereby permitting imaging of breast tumors within the useful lifetime of 99m Tc.…”
Section: Introductionmentioning
confidence: 99%
“…MAb fragments labeled with radioisotopes such as 99m Tc, 64 Cu, and 111 In [7][8][9][10][11] have been evaluated for their potential applications in the diagnosis of various cancers. [7][8][9][10][11] In this regard, Tang et al reported that 99m Tc-HYNIC-trastuzumab-Fab allowed imaging as early as 2 hours and more clearly at 6 and 24-hour postinjection, thereby permitting imaging of breast tumors within the useful lifetime of 99m Tc. 8 In similar lines, 64 Cu-labeled Fab fragment of ALT-836 ( 64 Cu-NOTA-ALT-836-Fab), a chimeric antihuman tissue factor MAb, showed fast tumor uptake and good tissue/muscle ratios on immuno-PET imaging of triple negative breast cancer patients performed on the same day.…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine was a small ligand of the cytokine receptor that was expressed on the surface of effector cells [47]. Many radio cytokine probes have already been applied in target imaging [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Hay que tomar en cuenta que el radionucléido 99m Tc se encuentra ampliamente disponible en centros de Medicina Nuclear, posee una química bien establecida y adecuadas propiedades nucleares ([t ½ = 6,04 h, Eγ = 140 KeV (89%)]; lo que junto a su bajo costo lo hacen un radionucleido indicado para la síntesis de este tipo de agentes de imagen. La química del marcado, con 99m Tc de forma directa o a través de agentes quelantes bifuncionales está bien establecida (28,29) y ha sido de amplio uso en nuestro departamento, donde disponemos de una plataforma ya establecida para la generación de este tipo de agentes de imagen (30)(31)(32)(33)(34).…”
Section: Cancer En Uruguay 2010-2014 Principales Sitios (Ordenados Po...unclassified